NEW DEVELOPMENT IN THE CITY OF PALANGKA RAYA, BETTER OR DISASTER? - Mandarin Guntur; Yunitha (Jurusan Arsitektur UPR, 2018)
City development and its movement have encouraged many people come in and make new ideas as occupants. They look this as a moment to take a chance and make a change in their life span. Hence, Palangka Raya as a capital city of Central Kalimantan, which actually a part of Indonesia should open its door to receive it as a unique elements of the city. This paper promotes two questions what government do. In addition, what people should do? Many people say that most development happen will bring disaster for the land where the city develop but countered it people say that city is a chance to life. Nevertheless, the important thing that should prior to know by the actor of the city is how to life on there and how to know the character of the city or place where they will be lived. This paper is aim at to promote rapid development happen in Palangka Raya since first development in 1957 until recently years. There are two kind of developments occurred in Palangka Raya, one side promotes preserved the city and its land and the other invited new disaster paradigms.